Analisis Pengaruh Perspektif Fraud Hexagon terhadap Kecurangan Laporan Keuangan dengan Kualitas Komite Audit sebagai Variabel Moderasi - Hartono, Felicia; Hasan Mukhibad (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2024)
This study aims to determine how the influence of financial targets, CEO educational background, number of board of commissioner meetings, auditor changes, frequent number of CEO's pictures, and participation in government projects on financial statement fraud with audit committee quality as a moderating variable in state-owned companies listed on the Indonesia Stock Exchange in 2018-2022. The population in this study were all state-owned companies listed on the Indonesia Stock Exchange, while the sample was 21 state-owned companies taken using purposive sampling techniques. The results of this study indicate that financial targets, CEO educational background, and frequent number of CEO's pictures have a positive and significant effect on financial statement fraud. The number of board of commissioner meetings, auditor changes, and participation in government projects do not affect financial statement fraud. The quality of the audit committee is able to weaken the influence of financial targets, CEO educational background, and frequent number of CEO's pictures on financial statement fraud. This research is expected to be useful for companies to identify factors that can influence financial reporting fraud.